Evaluation of Layered Graphene Prepared via Hydroxylation of Potassium-Graphite Intercalation Compounds. (3rd August 2014) - Wada, Takuya; Yasutake, Takuya; Nakasuga, Akira; Kinumoto, Taro; Tsumura, Tomoki; Toyoda, Masahiro
Abstract : Layered graphene was prepared via the hydroxylation of potassium-graphite intercalation compound (KC8 ) produced from exfoliated graphite flake powder. When a small amount of water was dropped onto the KC8 in an oxygen-free atmosphere, the stage structure of the intercalation compounds was broken, and agglomerated graphene was obtained. Sonication of this agglomerated graphene in buffered water containing sodium dodecyl sulfate followed by rinsing with hot water yielded gray samples. Using scanning electron microscopy, X-ray diffraction analysis, and Raman spectroscopy, the gray samples were determined to be composed of a few layers of graphene with an area of 20–100  μ m 2 and thickness of 1.7 nm. They were thinner than those obtained when starting with natural graphite.